2015
DOI: 10.1007/s11661-015-3169-9
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Repair Mechanism of Creep Damage in Fe-Au and Fe-Au-B-N Alloys

Abstract: The autonomous repair mechanism of creep cavitation during high-temperature deformation has been investigated in Fe-Au and Fe-Au-B-N alloys. Combined electron-microscopy techniques and atom probe tomography reveal how the improved creep properties result from Au precipitation within the creep cavities, preferentially formed on grain boundaries oriented perpendicular to the applied stress. The selective precipitation of Au atoms at the free creep cavity surface results in pore filling, and thereby, autonomous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 57 publications
(91 reference statements)
2
56
1
Order By: Relevance
“…In Figure 7, orientation maps for the solutionized Fe-Mo alloy are shown (a) before and (b) after creep at a stress of 160 MPa and a temperature of 838 K (565°C). In contrast to earlier measurements on creep-loaded solutionized Fe-Au alloys, [22] no indications for an extensive subgrain formation were observed. However, the average grain size for the Fe-rich bcc matrix phase derived from the EPMA figures was reduced from 33 lm before creep (Figure 7(a)) to 22 lm after creep (Figure 7(b)) (in accordance with the dynamic recrystallization assumed on the basis of the oscillating creep rate).…”
Section: B Scanning Electron Microscopycontrasting
confidence: 99%
See 2 more Smart Citations
“…In Figure 7, orientation maps for the solutionized Fe-Mo alloy are shown (a) before and (b) after creep at a stress of 160 MPa and a temperature of 838 K (565°C). In contrast to earlier measurements on creep-loaded solutionized Fe-Au alloys, [22] no indications for an extensive subgrain formation were observed. However, the average grain size for the Fe-rich bcc matrix phase derived from the EPMA figures was reduced from 33 lm before creep (Figure 7(a)) to 22 lm after creep (Figure 7(b)) (in accordance with the dynamic recrystallization assumed on the basis of the oscillating creep rate).…”
Section: B Scanning Electron Microscopycontrasting
confidence: 99%
“…Previous TEM studies on similar model alloys (Fe-Cu, Fe-Cu-B-N, Fe-Au, and Fe-Au-B-N) did not reveal a high dislocation density for undeformed specimens that were heated to 823 K (550°C). [16][17][18]22] Precipitates are also present along grain boundaries, as shown in Figure 8(c). Some grain boundaries are completely covered with a thin film of the Fe 2 Mo phase (see Figure 8(d)).…”
Section: Transmission Electron Microscopymentioning
confidence: 96%
See 1 more Smart Citation
“…The height of the creep cavity directly scales with the cavity radius a with h/a = (1 − cos ψ)/ sin (ψ) ≈ 0.77. Throughout the simulations the nominal concentration is chosen to be c 0 = 0.01, with an edge concentration of c 1 = 0.0001, in order to reflect the experimental situation for self healing in Fe-Au alloys [6,7,9]. As a consequence, the supersaturation c is comparable to the nominal concentration c 0 .…”
Section: Methodsmentioning
confidence: 99%
“…This mechanism was modelled by Karpov and coworkers [5]. Zhang and coworkers subsequently demonstrated that precipitation of substitutional solute leads to the self healing of creep cavities in Fe-Au and Fe-Mo alloys [6][7][8]. The creep defects and repairing precipitates were studied in detail for Fe-Au self-healing creep alloys, using X-ray nanotomography [9].…”
Section: Introductionmentioning
confidence: 99%